2015
DOI: 10.1016/j.joca.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus is more susceptible than cartilage to catabolic and anti-anabolic effects of adipokines

Abstract: Objective This study compared the effects on cartilage and meniscus matrix catabolism and biosynthesis of several adipokines implicated in osteoarthritis. Design Cartilage and meniscus explants were cultured for 1 or 9 days in serum-free medium alone or with 0.02, 0.2, or 2μg/ml of leptin, visfatin, adiponectin, or resistin. Media were supplemented with 3H-proline or 35S-sodium sulfate to evaluate protein and sulfated glycosaminoglycan (sGAG) accumulation on the last day of culture. Explants were assayed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…Consistent with previous observations of juvenile tissues (30), nitrite release was greater in cartilage than meniscus, perhaps due to greater cellularity of cartilage tissue (as evidenced by greater DNA content). While cumulative nitrite release was greater in co-cultured meniscus than in meniscus cultured alone, the nitrite release rate was unaffected.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous observations of juvenile tissues (30), nitrite release was greater in cartilage than meniscus, perhaps due to greater cellularity of cartilage tissue (as evidenced by greater DNA content). While cumulative nitrite release was greater in co-cultured meniscus than in meniscus cultured alone, the nitrite release rate was unaffected.…”
Section: Discussionsupporting
confidence: 91%
“…Adipose tissues can also produce a wide range of signaling molecules, and considerable recent interest has focused on the effects of fat-secreted factors on other tissues. In studies on the isolated effects of individual adipokines that can be produced by IFP, we found that several adipokines (most notably resistin) stimulated catabolic and anti-anabolic responses in cartilage tissues, with meniscus exhibiting greater sensitivity than articular cartilage (30). In contrast, the current co-culture study found that both cartilage and meniscus tissues displayed a modest anti-catabolic response to co-culture with fat (lower MMP-2 production) and cartilage but not meniscus exhibited a substantial anabolic response.…”
Section: Discussionmentioning
confidence: 99%
“…It has a positive correlation with obesity, insulin resistance, and chronic inflammation [153, 170] (Figures 1(a) and 1(b)). In murine models, cartilage and in human primary chondrocytes resistin was also found to induce MMP13, ADAMTS4, PGE 2 , TNF- α , and IL-8 (Figure 5 and Table 1) [171].…”
Section: Adipokines In the Pathobiology Of Osteoarthritic Cartilagementioning
confidence: 99%
“…A recent study showed that increase in body mass index (BMI) negatively regulated gene transcripts associated with extracellular matrix in human meniscus (6). In addition, meniscus was more susceptible than articular cartilage to catabolic effects of adipokines (7). These studies suggest that meniscus could be a primary tissue affected in obesity-linked OA.…”
Section: Introductionmentioning
confidence: 99%